2018
DOI: 10.3389/fnhum.2018.00359
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Pleasure: A Perspective Between Neuroscience and Psychoanalysis

Abstract: Pleasure is more than a mere sensory event, but rather it can be conceptualized as a complex, multiform experience involving memory, motivation, homeostasis, and, sometimes, negative affects. According to Freud, affect is a perceptual modality that registers the internal drive state of the subject rather than the objective experience of the external world, and the quality of this perceptual modality is calibrated in degrees of pleasure and displeasure. Within this conceptual framework, the aim of drive is alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…In fact, if by definition, the EMSs are stable and perpetuated over time, when patients with BAs experience emotional triggers, they will reactivate specific EMSs, and this will continue the vicious circle. Just as we said in the introduction, the EMSs are "comprised of memories, emotions, cognitions and bodily sensations regarding oneself and one's relationship with others, " it could be assumed that many alterations in cognition, in self-perceptions of emotions (i.e., alexithymia), and in the experience of pleasure (i.e., anhedonia), repeatedly reported in the literature among patients with BAs (Guillot et al, 2016;Moccia et al, 2017Moccia et al, , 2018, may be associated with the development and perpetuation of EMSs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if by definition, the EMSs are stable and perpetuated over time, when patients with BAs experience emotional triggers, they will reactivate specific EMSs, and this will continue the vicious circle. Just as we said in the introduction, the EMSs are "comprised of memories, emotions, cognitions and bodily sensations regarding oneself and one's relationship with others, " it could be assumed that many alterations in cognition, in self-perceptions of emotions (i.e., alexithymia), and in the experience of pleasure (i.e., anhedonia), repeatedly reported in the literature among patients with BAs (Guillot et al, 2016;Moccia et al, 2017Moccia et al, , 2018, may be associated with the development and perpetuation of EMSs.…”
Section: Discussionmentioning
confidence: 99%
“…In this case report, we may hypothesize that B’s compulsive search for an object of immediate pleasure through gaming may have resulted from maladaptive self-regulation strategies in a context where other forms of emotional self-regulation strategies (e.g., cognitive appraisal, seeking support) are inefficient. Using a psychodynamic view, gaming behavior can be regarded as a substitute for other common sources of pleasure at this age at an object level (e.g., poor family and peer relationship) and a narcissistic level (low self-gratification in a context of failure/poor academic or educational performance) (46, 47). The limitation of B’s affective domain to gaming may be partly explained by the necessity to restrict possible sources of pleasure/displeasure to limited and thus predictable factors in his environment.…”
Section: Discussionmentioning
confidence: 99%
“…When patients and caregivers were asked what they consider important in being cured from depression, caregivers emphasize the reduction of depressive symptoms, while patients take a greater interest in restoration of a meaningful life and in return of positive affect [71]. However, the concept of positive affect (and associated concepts: hedonic tone, pleasure, motivation, and reward) is at the risk of simplification: it has been suggested that a better disentangling of these concepts is helpful in understanding their neurobiological underpinnings [72].…”
Section: Is What Is Commonly Assessed What Matters To Patients?mentioning
confidence: 99%